Pelepasan dan Pemangsaan Kumbang Jelajah Paederusfuscipes (Coleoptera:Staphylinidae) Terhadap Telur Dan Larva Helicoverpa armigera (Lepidoptera: Noctuidae) - I Wayan Winasa; Dadan Hindayana; Sugeng Santoso (Institut Pertanian Bogor, 2007)
Paederus fuscipes is an important predators in soybean fields, including toward Helicoverpa armigera. Predation evaluation using a cage are very common, giving significant suppressed the exposed pest population. However, predation evaluation in open space is rarely conducted. This study was to investigate the dispersal capability of P. fuscipes, and to evaluate the effectiveness of the beetle release in the predation on H. Armigera eggs and larvae. Observations were made in a soybean field in Mekarwangi Village, Cianjur, during soybean planting season in 2005 and 2006. In the dispersal study, all beetles were collected from the field and tagged on the elitra. As many as 1187 tagged beetle were released. The dispersal was observed in the area within a radius of 40 m from the release point. In the predation study, eggs and larvae of H.armigera from laboratory rearing were used as the prey. Soybean plots with exposed prey were treated by releasing the beetle with different densities, i. e., 100-400 beetles, and a control. The released beetles were from laboratory rearing and beetles were collected from the field. The study indicated that the tagged beetles that were released to the soybean field actively move but their dispersal were relatively slow. Until 5 days after release, most beetles were remain in the area surrounding release point, within a radius of 5 m. Release of predators to the soybean field, suppressed H. armigera egg and larva populations for both vegetative and generative stages, but were not significantly different between treatment and control plots, except for the egg population on vegetative stage. It indicates that population of the natural predator in soybean field were very complex and potential to be used for controling pest populations. Thus, it is important to manage soybean field that can support the role of predators in the field. Key words: predator release, Paederus fuscipes, predation, Helicoverva armigera